Clofarabine/cyclophosphamide for debulking before stem cell transplantation. (August 2014) - Rabitsch, Werner; Böhm, Alexandra; Bojic, Marija; Schellongowski, Peter; Wöhrer, Stefan; Sliwa, Thamer; Keil, Felix; Worel, Nina; Greinix, Hildegard; Hauswirth, Alexander; Kalhs, Peter; Jaeger, Ulrich; et al.
Abstract Background Allogeneic haematopoietic stem cell transplantation (HSCT) is the only curative rescue therapy for patients (pts) with chemotherapy‐refractory acute leukaemia. Disease control prior to HSCT is essential for long‐term disease‐free survival after HSCT. Patients and Methods We have retrospectively analysed the outcome of 20 pts aged 21–64 years with refractory leukaemia (acute myeloid leukaemia, n = 16; acute lymphatic leukaemia, n = 4) who received debulking therapy with clofarabine (10 mg/m², days 1–4) and cyclophosphamide (200 mg/m², days 1–4; ClofCy) prior to HSCT. Results Clofarabine/cyclophosphamide (1–4 cycles) was well tolerated and resulted in a substantial reduction of leukaemic cells in all pts. HSCT was performed in 15 of 20 pts. After HSCT (myeloablative, n = 9; dose‐reduced, n = 6), all pts showed engraftment and full donor chimerism (related donors, n = 4 or unrelated donors, n = 11) and all pts achieved complete haematologic remission (CR). The median survival after HSCT is 531 days (range: 48–1462 days), and six pts are still alive after a median of 1245 days. Seven pts died after they had relapsed between days +152 and +1496. One patient died from acute graft‐versus‐host disease (day +48) and one from systemic fungal infection (day +87). Conclusion Clofarabine/cyclophosphamide is a novel effective treatment approach for pts with chemotherapy‐refractory acute leukaemia prior to HSCT. Whether this novel debulking protocol leads to improved long‐term outcome in pts with refractory leukaemias remains to be determined in forthcoming clinical studies.